PROBATE PROCEEDINGS AND A PREVIOUS ISSUE - Stojanovic, Natasa (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
The author’s attention is focused on the Serbian legislator’s solutions committed to solving a previous issue that may arise in a procedure for the conduct of heirship hearings. The research has been conducted with an aim to find reasoned answers to the following questions: Where is there a dispute on the application of law and Where is there a dispute on the facts concerning the right to inherit? How the legal standard “law that is less probable” should be understood? What characteristics of probate proceedings prevent solving of the arisen dispute in an equally quality manner as it is in litigation or administrative procedures? Why is solving of a dispute on the facts affecting the right to inherit relinquished to another court or administrative authority, when the authority conducting the heirship hearings has solved very complex issues beforehand? Is there any concern that the judge, that is to say the notary public conducting the heirship hearings in a concrete case will be competent enough to solve the arisen dispute, bearing in mind his/her professional competence, particularly that of notaries public? For the needs of this paper, legal-dogmatic, normative-legal, historical-legal and comparative-legal methods were used. The author, aiming to achieve a higher level of legal safety, a more consistent observance of the principle of efficiency and a more economical determination of inheritance-law effects on a person-s death, proposes adequate alterations and amendments of the regulations of extra-judicial proceedings.
Keywords: conduct of heirship hearings; right to inherit; previous issue; dispute over facts; dispute on the application of law